A Model of Developing creativity among Secondary and High School Students through the Arts of Relief Printing Processes - Al-Radaideh, Bssam; Al–Amery, Mohammed (Jordan Journal of Educational Sciences, 2013)
This research explore the relief printing arts as one of the most important disciplines of the fine arts, since it develop creativity, emotions and thinking skills among students through implementing the printing processes. The research presents the concepts of relief printing, its basics and its practical applications, as well as the aesthetic and the technical differences between the various relief printing mediums. This research confirms that if the students had the opportunity to experience this kind of applications, it will lead them towards creativity and self-development. Based on this finding, the researchers believes it is possible to teach these applications in the art education curricula, through suggesting a typical course in relief printing to students at the secondary and high schools levels, with taking into consideration planning strategies, teaching instruments and methods, learning process and evaluation. To reach the highest level of understanding the applications techniques, the research was provided with digital sources and links.